T-cell-dependent and T-cell-independent mechanisms of tolerance to glucuronoxylomannan of Cryptococcus neoformans serotype A. - Sundstrom, J B (1993)
Glucuronoxylomannan (GXM), a type 2 T-independent antigen, is the major component of the capsular polysaccharide (CnCAP) of Cryptococcus neoformans. Previous studies have described the tolerogenic effects of high doses of CnCAP on the specific humoral response. In this investigation, evidence for both high-dose and low-dose tolerance to GXM is presented. BALB/cBy female mice, primed with either 5 ng or 50 micrograms of GXM, then coimmunized 3 days later with immunogenic doses of both GXM and type 3 pneumococcal polysaccharide (SSS-III), showed an antigen-specific inhibition in their splenic plaque-forming cell (PFC) responses to GXM compared with control groups primed with normal saline. SSS-III PFCs remained unchanged between GXM-primed and normal saline-primed groups. Low-dose tolerance appeared to be T dependent, whereas high-dose tolerance appeared to be T independent. Low-dose tolerance to GXM could not be induced in athymic BALB/c nu/nu mice, whereas high-dose tolerance in the same mice could be induced. Furthermore, low-dose tolerance was adoptively transferred with B-cell-depleted splenocytes to naive BALB/c mice, while high-dose tolerance was not. Complement-mediated depletion of CD4+ but not CD8+ splenocytes from low-dose-primed mice abrogated the transfer of low-dose tolerance. These findings indicate T-dependent and T-independent mechanisms of antigen-specific B-cell tolerance to GXM in BALB/c mice at low and high antigen doses, respectively.